Implementasi Pengadaan Barang Dan Jasa Melalui Electronic Procurement Di PT. PLN (Persero) Unit Induk Distribusi Kalimantan Selatan Dan Kalimantan Tengah - Azizah, Nilna Azizah; Maryono, Maryono (JURNAL BISNIS DAN PEMBANGUNAN, 2024)
This study aims to identify the implementation of E-Procurement at PT PLN (Persero) South Kalimantan and Central Kalimantan Distribution Main Unit, especially the obstacles confronted. E-Procurement, which uses the internet as a means of information and communication, is expected to increase the efficiency of goods and services procurement. This research uses a qualitative approach with a focus on the implementation of E-Procurement at PT PLN (Persero) South Kalimantan and Central Kalimantan Distribution Main Unit. The data was collected through interviews, observations, documentation studies, and analyzed using the Miles and Huberman model. The results of the study found that the implementation of E-Procurement at PT PLN (Persero) South Kalimantan and Central Kalimantan Distribution Main Unit is well implemented based on indicators of quantity, quality, and timeliness. However, there are obstacles in the direct procurement process. The solution that has been done to deal with the obstacles of the implementation is to provide comprehensive counseling for Electronic Procurement users